A COMPREHENSIVE REVIEW ON THE APPLICATIONS OF ECOTOURISM IN BIOLOGICAL CONSERVATION AND ENVIRONMENTAL EDUCATION - Geetha N B; Lavanya C; Ezhilarasi; Raju S (The Bioscan, 2025)
Ecotourism, as a field of study and practice, remains in a formative stage with ongoing debates surrounding its definition, planning, and implementation. The lack of a universally accepted definition reflects the diversity of perspectives and objectives within ecotourism discourse. This review contends that rigid definitions may be unnecessary if the focus remains on the underlying principles and objectives of ecotourism. Broadly, the concept encompasses three key themes: natural conservation, environmental education, and sustainability—incorporating both economic and social dimensions. Each of these elements offers distinct benefits but also presents challenges, particularly when commercial interests outweigh ecological and ethical considerations. The credibility of ecotourism hinges on transparent practices, ethical marketing, and the prevention of consumer exploitation. This article critically explores the foundational themes of ecotourism, analyzing its ecological, educational, and sustainable dimensions. It also reflects on the evolving dynamics of the tourism industry and discusses future directions for ecotourism research and practice.